PENERAPAN STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PEMPEK RAJO SALMAN 26 ILIR PALEMBANG DALAM PERSPEKTIF EKONOMI ISLAM: Perspektif Ekonomi Islam - Meisy Putri Qonitah Henny Oktavia; Hilda; Safitri Asrol (Lentera Ilmu Madani, 2026)
Marketing strategy plays an important role in increasing sales and maintaining business competitiveness. This study aims to analyze the marketing strategies implemented by Pempek Rajo Salman 26 Ilir Palembang in increasing sales and to examine them from the perspective of Islamic economics. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The results show that Pempek Rajo Salman applies product, price, place, and promotion strategies effectively to increase sales. From the perspective of Islamic economics, these strategies are in accordance with the principles of honesty, fairness, and responsibility. Therefore, the implementation of marketing strategies contributes to business growth while reflecting Islamic business ethics. Keywords:MarketingStrategy,Sales,IslamicEconomics,MSMEs.